2014
DOI: 10.5194/acp-14-5349-2014
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol formation and composition from the photo-oxidation of methyl chavicol (estragole)

Abstract: Abstract. The increasing demand for palm oil for uses in biofuel and food products is leading to rapid expansion of oil palm agriculture. Methyl chavicol (also known as estragole and 1-allyl-4-methoxybenzene) is an oxygenated biogenic volatile organic compound (VOC) that was recently identified as the main floral emission from an oil palm plantation in Malaysian Borneo. The emissions of methyl chavicol observed may impact regional atmospheric chemistry, but little is known of its ability to form secondary orga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 87 publications
1
29
0
Order By: Relevance
“…C6H8O7 was identified as citric acid in the pollen sample and mountain particle sample in previous studies (Fu et al, 2008;Wang et al, 2009;Jung and Kawamura, 2011) and C9H8O4 are probably homophthalic acid derived from e.g. estragole (Pereira et al, 2014). For the Guangzhou− samples, besides the formulas of C8H6O4 and C6H8O7 discussed above, C4H6O4…”
Section: Cho Compoundsmentioning
confidence: 80%
See 1 more Smart Citation
“…C6H8O7 was identified as citric acid in the pollen sample and mountain particle sample in previous studies (Fu et al, 2008;Wang et al, 2009;Jung and Kawamura, 2011) and C9H8O4 are probably homophthalic acid derived from e.g. estragole (Pereira et al, 2014). For the Guangzhou− samples, besides the formulas of C8H6O4 and C6H8O7 discussed above, C4H6O4…”
Section: Cho Compoundsmentioning
confidence: 80%
“…According to previous studies, C8H6O4, C7H6O2 and C7H6O3 are suggested to be phthalic acid, benzoic acid and monohydroxy benzoic acid, respectively, which are derived from naphthalene (Kautzman et al, 2010;Riva et al, 2015;Wang et al, 2017;He et al, 2018;Huang et al, 2019). C8H8O2 and C8H8O3 are likely 4-hydroxy acetophenone and 4-methoxybenzoic acid which could be derived from estragole (Lee et al, 2006;Pereira et al, 2014). For the Shanghai− samples, besides C8H6O4, C7H6O3 and C7H6O2, formulas of C6H8O7 and C9H8O4 with DBE values of 3 and 6 were observed with high peak abundances.…”
Section: Cho Compoundsmentioning
confidence: 92%
“…As configured, the sampling setup enables a blank and chamber measurement to be obtained in a 7 min cycle, a substantially higher time resolution than most other semicontinuous sampling methods (Bateman et al, 2009;Pereira et al, 2014) or collection onto filters. It is comparable to the recent highly time-resolved particle-into-liquid-sampling measurements of Zhang et al (2015).…”
Section: Time Series Of Individual Particle-phase Ionsmentioning
confidence: 99%
“…A number of recent studies have therefore developed online or semi-continuous atmospheric-pressure ionisation (API) MS techniques (Bateman et al, 2009;Brüggemann et al, 2015;Clark et al, 2014;Nah et al, 2013;Pereira et al, 2014;Vogel et al, 2013;Zhang et al, 2015;Zhao et al, 2017b). In this paper, we focus on the application of one such approach to organic aerosol analysis, namely extractive electrospray ionisation (EESI) MS.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review shows that polar nitroaromatic compounds (NACs) are partially responsible for optical properties of ambient urban particles, thereby influencing their aerosol radiative forcing . Nitroaromatic compounds are typically associated with products from aromatic oxidations, biogenic oxidations, and biomass burning . In addition, a broad range of NACs have been detected in chamber irradiations of these precursors, as well as from field samples .…”
Section: Introductionmentioning
confidence: 99%